The Effectiveness of Using the Group Investigation Model in Improving Mathematics Motivation in SMK Dwi Tunggal 1 Tanjung Morawa - Fadilah; Halomoan, T.H; Priyanda, R (Jurnal Dimensi Matematika, 2020)
This research aims to find out whether by applying a group investigation leraning model can increase student’s motivation to learn mathematic grade X in SMK Dwi Tunggal 1 Tanjung Morawa. The research instruments used were observation and questioner. The observations used are statements of the learning process. Observation consists of observation sheets on the effectiveness of student learning, and observation of student learning motivation.The population this study is Students Class off X SMK Dwi Tunggal 1 Tanjung Morawa, while the sample in this study was a class off X-AP SMK Dwi Tunggal 1 Tanjung Morawa. From the results of the study can be seen an in crease student motivation to learn mathimatics by using a learning model of investigation b 75% at the first meeting and is categorized as effective, while at the second meeting it reaches 80% and is categorized as effective. Thereofere the use of the group investigation learning model is effective in creasing the motivation to learn mathematic in students of SMK Dwi Tunggal 1 Tanjung Morawa.